The Influence of Thermocycling and Ultraviolet Aging on Surface Characteristics and the Repair Bond Strength of CAD/CAM Resin Nanoceramics - Beyza Unalan Degirmenci; Alperen Degirmenci; Zelal Seyfioglu Polat (Journal of Functional Biomaterials)
Background: The durability of computer-aided design/computer-aided manufacturing (CAD/CAM) resin nanoceramics in the oral environment is influenced by aging factors such as thermocycling and ultraviolet (UV) exposure. This study investigates the impact of these aging processes on surface characteristics and repair bond strength. Methods: CAD/CAM resin nanoceramic samples were divided into the following five groups: control (non-aged), 1-year and 5-year thermocycling, and 1-year and 5-year UV aging (n = 12). For the thermocycling procedure, the parameters employed were a temperature range of 5–55 °C with dwell times of 20 s per bath and 10,000 and 50,000 cycles; for the ultraviolet aging process, the parameters were established at a wavelength of 340 nm, an intensity of 0.55 W/m², and durations of 300 h and 1500 h. Surface roughness, microhardness, and repair bond strength were analyzed through profilometry, Vickers microhardness testing, and shear bond strength assessment, respectively. SEM, AFM, and XRD analyses were performed for structural evaluation. Results: Both thermocycling and UV aging significantly increased surface roughness (p < 0.001) while reducing microhardness and repair bond strength (p < 0.001). UV aging had a more pronounced effect, particularly after five years, leading to the highest surface roughness (Ra: 61.77 μm; Rz: 271.57 μm) and lowest microhardness properties (63.13). EDAX analysis indicated matrix degradation and an increase in inorganic filler exposure. Conclusions: Aging significantly affects the surface characteristics of CAD/CAM resin nanoceramics, with UV aging exhibiting the most detrimental impact. These findings highlight the necessity of considering long-term material stability in dentistry.